The Integration of Social Media in Developing English Vocabulary Skills and Its Impact on Students Learning Motivation - Darman Pangaribuan; Mhd. Azan Junanda Cahya Hartono; Varhan Kudadiri; Febry Priayi Irjul Prakasa; Jonris Tampubolon (EduInovasi: Journal of Basic Educational Studies, 2025)
Learning English as a Foreign Language (EFL) presents challenges, particularly in vocabulary acquisition. This study examines the integration of social media, specifically Instagram, in enhancing students' vocabulary skills and its impact on learning motivation. A quantitative experimental design was employed, involving pre-tests, treatment, and post-tests on students from STKIP Pangeran Antasari. The findings indicate a significant improvement in vocabulary acquisition, with post-test scores showing an increase from an initial 33.33% mastery level to 93.33%. Moreover, students' motivation significantly increased, as evidenced by post-questionnaire results. The study suggests that social media can be an effective supplementary tool for vocabulary learning, providing interactive and engaging learning experiences.